ANALISIS PENGARUH PERSON ORGANIZATION FIT DAN PERSON JOB FIT TERHADAP TURNOVER INTENTION DENGAN WORK ENGAGEMENT SEBAGAI VARIABEL INTERVENING (Studi pada Karyawan BPR Bank Surya Yudha Kantor Pusat Banjarnegara) - Saputra, Anas Tegar; Djastuti, Indi (Diponegoro Journal of Management, 2021)
ABSTRACT Turnover intentions have been the focus of attention for many academics and industry over the years. This is because when the turnover intention is left alone, it will cause various problems within the company. The research is discussed to study and to analyze the effect of person organization fit and person job fit variables on turnover intention through work engagement as an intervening variable. This study uses primary and secondary data, and population in this study were operational employees of BPR Bank Surya Yudha Head Office Banjarnegara. The data method used in this research is distributing questionnaires using the census method or total sampling. The data analysis technique used in this study was using the SPSS version 25 application, with the method of path analysis and multiple regression. Data analysis was carried out including validity test, reliability test, classical assumption test, t test, F test, determination coefficient test, and also sobel test to determine the mediation effect. The results of statistical test show that person organization fit variable has a negative and significant effect on turnover intention, and has a positive and significant effect on work engagement. Person job fit also has a negative and significant effect on turnover intention and has a positive and significant effect on work engagement. In addition, it is also known that the work engagement variable can mediate the relationship between person organization fit and person job fit on turnover intention..